Ena drives invasive macrophage migration in Drosophila embryos - Philippa K. Tucker; Iwan R. Evans; Will Wood (The Company of Biologists, 2011)
SUMMARY It is seldom the primary tumour that proves fatal in cancer, with metastasis the fundamental pathological process for disease progression. Upregulation of Mena, a member of the evolutionarily conserved Ena/VASP family of actin cytoskeletal regulators, promotes metastasis and invasive motility of breast cancer cells in vivo. To complement in vitro studies of Ena/VASP function in fibroblasts, we manipulated levels of Ena, the Drosophila homologue of Mena, in migrating embryonic macrophages (haemocytes). Consistent with data from fibroblasts in vitro, Ena localises to regions of actin dynamics within migrating haemocytes, stimulates lamellipodial dynamics and positively regulates the number and length of filopodia. However, whereas Ena overexpression in fibroblasts reduces migration speeds, overexpressing Ena in haemocytes leads to a dramatic increase in migration speeds, more closely resembling the increased motility of breast cancer cells that overexpress Mena. We provide evidence that this key difference is due to spatial constraints imposed on cells within the three-dimensional environment of the embryo; this might explain how Mena can be used to promote aggressive migratory behaviour during cancer progression.